Pengaruh Citra Merek. Kualitas Produk, dan Kepuasan Pelanggan Terhadap Loyalitas Pelanggan pada Produk Teh Pucuk Harum di Surabaya - Dimas Maulana Putra; Siti Ning Farida (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to analyze the influence of brand image, product quality, and customer satisfaction on customer loyalty for Teh Pucuk Harum products in Surabaya City. This study employs a quantitative method approach. The population used in this study is consumers of Teh Pucuk Harum in Surabaya. The sample size in this study was determined using the Slovin formula, resulting in a required sample of 100 respondents. Data were collected through questionnaires and analyzed using multiple linear regression analysis. The results show that brand image, product quality, and customer satisfaction simultaneously have a significant effect on customer loyalty. However, partial analysis reveals that only customer satisfaction has a significant influence on customer loyalty. Brand image and product quality, although showing a positive influence, do not have a significant partial effect on customer loyalty.